2020
DOI: 10.1055/s-0040-1707269
|View full text |Cite
|
Sign up to set email alerts
|

Deoxygenative Transition-Metal-Promoted Reductive Coupling and Cross-Coupling of Alcohols and Epoxides

Abstract: The prospective utilization of abundant, CO2-neutral, renewable feedstocks is driving the discovery and development of new reactions that refunctionalize oxygen-rich substrates such as alcohols and polyols through C–O bond activation. In this review, we highlight the development of transition-metal-promoted reactions of renewable alcohols and epoxides that result in carbon–carbon bond-formation. These include reductive self-coupling reactions and cross-coupling reactions of alcohols with alkenes and arene deri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…The deoxygenative transition-metal-catalyzed cross-coupling of two unprotected alcohols has scarcely been reported. For further discussion on related cross-electrophile coupling, we recommend the account from Gong on the use of alcohol derivatives and the review from Nicholas that describes diverse applications of alcohols and epoxides …”
Section: Deoxygenative Functionalizationmentioning
confidence: 99%
See 1 more Smart Citation
“…The deoxygenative transition-metal-catalyzed cross-coupling of two unprotected alcohols has scarcely been reported. For further discussion on related cross-electrophile coupling, we recommend the account from Gong on the use of alcohol derivatives and the review from Nicholas that describes diverse applications of alcohols and epoxides …”
Section: Deoxygenative Functionalizationmentioning
confidence: 99%
“…For further discussion on related cross-electrophile coupling, we recommend the account from Gong on the use of alcohol derivatives 193 and the review from Nicholas that describes diverse applications of alcohols and epoxides. 194 2.2.4. π-Activated Alcohols with Arenes, Alkenes, Enols, and Other π-Nucleophiles. π-Activated alcohols can be coupled with a range of unsaturated compounds such as alkenes, alkynes, and arenes via cross-coupling and related transformations to forge new C−C bonds.…”
Section: π-Activated Alcohols With Other Electrophilesmentioning
confidence: 99%
“…Generally, these approaches mostly involve a two-electron pathway, and require a transition-metal catalyst or a good leaving group. [20][21][22][23] In 1967, Mitsunobu et al found that alcohols could undergo phosphorylation to give phosphate esters in the presence of Ph 3 P and diethyl azodicarboxylate (DEAD). 24 With its broad scope, stereospecificity and mild reaction conditions, the Mitsunobu reaction has become widely used.…”
mentioning
confidence: 99%